Pembinaan Prestasi Atlet Karate Di Dojo Garuda Karate Kecamatan Bangsri Kabupaten Jepara (Universitas Negeri Semarang, 2021)
The development of karate in Indonesia has progressed, one of which is in Jepara Regency. Dojo Garuda is one of the clubs that provides guidance for karate achievements from an early age. Dojo Garuda is able to produce talented seeds who win many championships. The purpose of this study was to determine the coaching process carried out by the Garuda Dojo. Methods of data collection using interviews, observation, and documentation. Data analysis in this study is data reduction, display data, and verification. The result of this research is athlete development starting from early childhood to high school level. The training program consists of training program phases, namely general and special preparation stages, pre-competition and competition stages, and running training according to the training program. The coach has a coaching license. The facilities and infrastructure that are owned are adequate, with the existence of their own training building and equipped with mattresses and other facilities to support the training. Good and active organizational structure. Funding from regular athlete fees and sponsorships. Achievements include regional to international levels. Awards for athletes from their respective athletes' schools as well as from the district government, the dojo have not yet given awards. The conclusion of this research is that the guidance has been good but the appreciation is still lackings.